Determination of 19 polyphenolic compounds in tea by ultra-high performance liquid chromatography combined with quadrupole-time of flight mass spectrometry - Jian Li; Junmei Ma; Yan Zhang; Lei Zheng (Food Science and Human Wellness)
A rapid method was presented for the determination of 19 polyphenols in tea by ultra-high performance liquid chromatography coupled with quadrupole-time of flight mass spectrometry (UPLC-Q-TOF MS). Tea samples were extracted by 50% (V/V) ethanol, then separated by Waters Acquity BEH C18 column using a binary solvent system composed of acetonitrile and water (0.1% formic acid) by gradient elution. The analytes were determined by Q-TOF MS in TOF MS and information dependent acquisition (IDA)-MS/MS mode. The results showed that mass accuracy error of the 19 polyphenols were lower than 5.0 × 10–6, good linear relationship was got in range of 0.2–500 μg/L and correlation coefficient was higher than 0.9990. The LOD was in the range of 0.002–0.100 mg/kg and the LOQ was in the range of 0.004–0.200 mg/kg. Recovery of the method was in range of 78.4%–109.2% with spike levels of 0.004–2.000 mg/kg, relative standard deviations were lower than 10%. The method was simple, rapid and accurate. It could be used for the rapid screening and quantitative analysis of 19 polyphenols in tea.